Definitions of Non-Permanent Employment and the Problems of Its Measurement in Russia - Татьяна Сергеевна Карабчук (Journal of Economic Sociology, 2010)
The paper is devoted to the phenomenon of non-permanent employment in Russia focusing on the problem of definitions and measurement. After an overview of main approaches evaluating non-permanent employment, the author provides a definition which corresponds to the statistical categories applied in international studies. It gives a good opportunity to analyze the data from comparative perspective. The paper also deals with the issues labour legislation regulating non-permanent employment. The author estimates the structure and dynamics of the temporary employment in Russia which makes up to 8 million people in 2008.